2016
DOI: 10.1016/j.compfluid.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Low-Re flow past an isolated cylinder with rounded corners

Abstract: Highlights• DNS on the separation and transition of flow past a partially rounded cylinder.• The effect of the corner radius of the cylinder is studied.• Investigation on time-averaged flow, unsteady flow, turbulent statistics and 3D flow pattern.• There are drastic variations of the flow pattern between the square cylinder and the partially rounded cylinder, and between the latter and the circular cylinder.• Non-time-periodicity is significant in the shear layer and at the reattachment point. AbstractDirect n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…The codes for the direct simulation and stability-sensitivity analysis have been successfully employed in our earlier works 2841 for low- Re flow across one single or two tandem cylinders of various geometries, and the results are in good agreement with the benchmark results in the literature through careful comparisons (see, e.g., Table 1 in Zhang et al. 35 and Table 3 in Zhang et al.…”
Section: Numerical Setupsupporting
confidence: 52%
See 1 more Smart Citation
“…The codes for the direct simulation and stability-sensitivity analysis have been successfully employed in our earlier works 2841 for low- Re flow across one single or two tandem cylinders of various geometries, and the results are in good agreement with the benchmark results in the literature through careful comparisons (see, e.g., Table 1 in Zhang et al. 35 and Table 3 in Zhang et al.…”
Section: Numerical Setupsupporting
confidence: 52%
“…The discretized equations are solved using our in-house second-order code based on fractional step method 27 which has been well verified in our earlier works. 2841 The time step size is around 0.005 d / U 0 . The simulations are initialized with ( u, v, p ) = (1.0, 0.0, 0.0) and no artificial perturbation is added; the flow is first steady but then loses its stability as integrating in physical time and becomes perfectly time-periodic after a certain duration as reflected by the shedding vortices.…”
Section: Numerical Setupmentioning
confidence: 99%
“…For the super-critical two-and three-dimensional flows at Re∼O(10 2 −10 3 ), Sohankar et al [16] found that the aerodynamic quantities, such as the mean and fluctuating lift and drag coefficients, are substantially affected by the cylinder geometry. Recent numerical and experimental studies [17][18][19] confirmed that the flow pattern is determined by the corner radius of a partially rounded cylinder. By rounding the corners of a square cylinder with a small radius of curvature, the formation of the shedding vortices are initialized further downstream away from the cylinder compared with both the circular and square geometries, and results in the streamwise expansion of the recirculation bubbles.…”
Section: Introductionmentioning
confidence: 95%
“…The two-dimensional direct simulation is performed by our in-house code used in previous studies [19,[24][25][26]. The governing equations (1) are discretized on the grid using a second-order central difference scheme.…”
Section: Direct Simulationmentioning
confidence: 99%
“…The governing equations were solved using our in-house finite difference code which has been well validated for flow across bluff bodies. 2735 The time marching in one physical step consists of three sub-steps including the predictor step for velocity, the solution of pressure and the corrector step for velocity. The differential equations for the sub-steps are formulated as:…”
Section: Numerical Setupmentioning
confidence: 99%